Rancangan Press Tool Pembuat Komponen Penumpu Dongkrak Pantograf - Revaldy Maiman; Ravi Pratama Syael; Mulyadi Mulyadi; Daddy Budiman; Yuli Yetri (Manutech : Jurnal Teknologi Manufaktur, 2022)
Press Tool is designed to be able to make mass and uniform products in a relatively short time. One of the products that can be produced using a press tool is the supporting component of the pantograph jack. Pantograph jacks are used in the automotive industry. The need for this product increases along with the increasing demand for motorized vehicles, especially cars. The production stages of supporting components using a press tool include: trim stop, piercing, notching, bending, cropping and deep drawing. Press tool design methods include: determining the design and supporting dimensions, calculation, simulation, and analysis using solidworks simulation analysis. The thickness of the plate that is safe to use for the manufacture of supports is 3 mm with ST 37 material. The planning dimensions of the press tool are (320 x 250 x 217) mm. Press tool components include: shank, punch, dies, top plate, bottom plate, pressure plate, punch holder, stripper plate, guide pillar, guide bush, bolt, and guide pen. The materials used to make press tool components include: ST 37, ST 42, brass, HASCO standard, AISI standard, and Polman Bandung standard. The total force that occurs in the manufacture of supports is 442798.2 N.